Effect of Time Interval From Diagnosis to Treatment on Economic Burden in Families of Children With Autism Spectrum Disorder - Zhou, Wensu; Wu, Kui; Chen, Shu; Liu, Dan; Xu, Huilan; Xiong, Xiyue (Frontiers in Psychiatry, 2021)
The study aimed to investigate the economic costs in families of children with autism spectrum disorder (ASD) and explored how the time interval from diagnosis to treatment influenced the economic costs. It was a cross-sectional study recruited families with autistic children in Changsha city, Hunan province of China during March to November 2018. A self-designed questionnaire was applied to collect ASD-related economic costs in the two vital periods including 12-month period after diagnosis and the most recent 12- month during the course of ASD. In total, 136 families with autistic children completed the interview. The results showed 46.3% of children started intervention within one month. The median of total economic costs of these families in the 12-month period after diagnosis and the most recent 12-month were 26,502.26 RMB and 29,411.91 RMB, respectively. Compared with the time interval shorter than one month, time interval over six months was significantly associated with more severe direct economic costs ( β=0.308, 95%CI=0.177, 1.254), inpatient/outpatient and drugs costs ( β=0.276, 95%CI=0.104, 1.181 ), direct non-medical costs ( β=0.287, 95%CI=0.140, 1.206 ) and total economic burden ( β=0.311, 95%CI= 0.186, 1.262), besides, time interval between four to six months was significantly related to more severe indirect costs ( β=0.230, 95%CI=0.098, 1.363) in the 12-month period after diagnosis. Similarly, time interval between one to three months was significantly associated with more severe direct non-medical costs ( β=0.198, 95%CI=0.004, 1.013) in the 12-month period after diagnosis. However, time interval from diagnosis to treatment was not correlated to economic costs in the recent 12-month. In the long term, shorten the time interval from diagnosis to treatment would reduce the economic burden on families, especially in the 12-month period after diagnosis.